The effect of reap strategy on students’ reading comprehension in reading descriptive text - Tampubolon, Marlina; Sinaga, Dwi Pebrina; Harahap, Nurul Husnah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The aims of this study are to find out whether the application REAP strategy is effective to affect students’ reading comprehension in reading descriptive text. This research was conducted by using in experimental quantitative. the writer found that the REAP Strategy significantly affects the students’ reading comprehension. There is a significant difference of mean score got from both of the experimental group (20.03) and the control group (12.93). The t-observe > t-table (P = 0.05) df (58), or 3.38 > 2.000 (P = 0.05). It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It can be concluded that there is a significant effect of applying REAP Strategy on teaching reading comprehension. The students who were taught reading comprehension by using REAP Strategy (experimental group) got the higher scores than the students who were not taught by using conventional way (control group). by using REAP strategy the students can understand Descriptive without trying hard to understand the meaning of each word in that text not only in Descriptive text but also in another text types like: Narrative and Report.